Emergency Nursing Care for Patients with Acute Myocardial Infarction (AMI) with Acute Pain Nursing Problems - Mohammad Iqbal Gadafi; Naylil Mawadda Rohma (INDOGENIUS, 2026)
Background & Objective: Acute myocardial infarction (AMI) is one of the clinical manifestations of cardiovascular disease, which remains the leading cause of death worldwide. AMI, better known as a heart attack, occurs due to a blockage in blood flow to the heart muscle, causing the death of myocardial cells (cardiomyocytes). One of the most common clinical manifestations found in patients with AMI is chest pain. This study aims to analyze the results of nursing care for acute pain problems in patients with Acute Myocardial Infarction at Dr. Harjono Regional General Hospital, Ponorogo Regency. Method: The type of research used is descriptive qualitative in the form of a case study with a documentation study approach. The subjects in this study were patients with acute pain nursing problems who were treated in the emergency room and ICVCU. Data collection was conducted through interviews, observations, and documentation studies. Nursing care was provided for three days, from May 10 to 12, 2025. Result: The results of the study showed that patients experienced acute pain related to physiological injury agents. Conclusion: After nursing intervention for 3 x 24 hours, the nursing problems were partially resolved, as evidenced by the achievement of five out of five outcome criteria, namely reduction in pain, grimacing, moaning, restlessness, and pain avoidance behavior.